2014
DOI: 10.1167/iovs.13-12660
|View full text |Cite
|
Sign up to set email alerts
|

Difluprednate 0.05% Versus Prednisolone Acetate 1% for Endogenous Anterior Uveitis: A Phase III, Multicenter, Randomized Study

Abstract: PURPOSE. Endogenous anterior uveitis (AU), when untreated, may lead to vision loss. This study compared the safety and efficacy of difluprednate versus prednisolone acetate for the treatment of this condition.METHODS. This phase III, double-masked, noninferiority study randomized patients with mild to moderate endogenous AU to receive difluprednate 0.05% (n ¼ 56) four times daily, alternating with vehicle four times daily, or prednisolone acetate 1% (n ¼ 54) eight times daily. The 14-day treatment period was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 27 publications
7
50
0
Order By: Relevance
“…Sheppard JD, in his study concluded that difluprednate 0.05% four times daily is equivalent to prednisolone acetate 1% eight times daily in management of intra ocular inflammation in endogenous anterior uveitis [17].…”
Section: Iop Assessmentmentioning
confidence: 99%
“…Sheppard JD, in his study concluded that difluprednate 0.05% four times daily is equivalent to prednisolone acetate 1% eight times daily in management of intra ocular inflammation in endogenous anterior uveitis [17].…”
Section: Iop Assessmentmentioning
confidence: 99%
“…The 0.5% difluprednate ophthalmic emulsion (Durezol, Alcon Laboratories, Fort Worth, TX) has high glucocorticoid receptor affinity, tissue penetration, and bioavailability ). Studies in patients with endogenous anterior uveitis have shown non-inferiority of difluprednate 0.05% dosed four times daily compared to prednisolone acetate 1% dosed eight times daily for 14 days Sheppard et al 2014). Clinically important IOP elevations were observed in 8.9-12% of eyes that received difluprednate compared to 3.7-5% of eyes that received prednisolone acetate 1%.…”
Section: Local Corticosteroidsmentioning
confidence: 97%
“…10,11 Difluprednate ophthalmic emulsion 0.05% is a topical ocular corticosteroid that has been approved since 2008 for use in adults, initially for treatment of inflammation and pain associated with ocular surgery, and subsequently for treatment of endogenous anterior uveitis. 12,13 Recent studies in adults have shown that difluprednate treatment is associated with rapid resolution of both inflammation and pain associated with ocular surgery. 9 Phase 3 studies in adults have shown that difluprednate 0.05% four times daily is well tolerated and noninferior to prednisolone acetate 1% eight times daily for treatment of endogenous anterior uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…9 Phase 3 studies in adults have shown that difluprednate 0.05% four times daily is well tolerated and noninferior to prednisolone acetate 1% eight times daily for treatment of endogenous anterior uveitis. 12,14 Children have a greater propensity for postoperative inflammation than adults. 3,8,15 The safety of topical difluprednate after ocular surgery in children has not been previously established.…”
Section: Introductionmentioning
confidence: 99%